Associations Between Organizational Culture, Workplace Health Climate, and Employee Smoking at Smaller Workplaces. (March 2019) - Kava, Christine M; Parker, Edith A; Baquero, Barbara; Curry, Susan J; Gilbert, Paul A; Sauder, Michael; Sewell, Daniel K
Background: Smaller workplaces frequently employ low-wage earners, who have higher smoking rates. Organizational culture and workplace health climate are two characteristics that could influence employee smoking. The purpose of this study was to examine the associations between organizational culture, workplace health climate, and smoking among employees at small (20-99 employees) and very small (<20 employees) workplaces. We proposed the following hypotheses: a stronger clan culture will be associated with a better workplace health climate (HP1); a better workplace health climate will be associated with lower odds of current smoking (HP2); and there will be an association between workplace health climate and smoking intensity (HP3) and between workplace health climate and quit intention (HP4). Methods: Executives and employees completed separate online questionnaires. Data collection occurred between June and October 2017. We used regression and Fisher's exact tests to answer study hypotheses. Results: Workplaces with stronger clan cultures had a better workplace health climate (b = 0.27, P < .05), providing support for HP1. A better workplace health climate was associated with lower odds of being a current smoker (odds ratio [OR] = 0.08; 95% confidence interval [CI]: 0.01, 0.53), providing support for HP2. No significant relationship existed between workplace health climate and smoking intensity ( P = .50) or between workplace health climate and intention to quit smoking ( P = .32); therefore, HP3 and HP4 were not supported. Conclusion: Certain culture types may inform an organization's health climate. Despite a lower likelihood of current smoking in workplaces with better health climates, a better health climate may not be sufficient to produce changes in smoking behavior and intentions.